Heritage and Identity: to Teach History with the Social Change (Tempo e Argumento, 2021)
Making history useful for students is one way of defining the main goal of teachers who need a general framework to act. To define the objectives is particularly important in the context of social changes. This general framework must be based on two levels: the cognitive, where teaching-learning of history is defined, and the social, where the consequences of the former, used at schools, influences the sense of usefulness. Between both, the role of heritage is pivotal. The rationale of the approach proposed in this paper can be explained through two main arguments: 1) Historical discipline is a scientific knowledge, although it is usually associated more to memorize than to reflect. In that sense, heritage can be treated as a historical source. Students can create multiple discourses if they have competences related to scientific, critical and creative thinking; 2) As history, heritage is a cornerstone in developing a sense of identity and should be used as such in schools to form citizens. With this in mind, three driving vectors are proposed where the usefulness of history depends on its treatment in schools: a) consumer collective identity/heritage-object/ insolvent historical knowledge; b) hard collective identity/heritage-commemoration/single history; and c) weak collective identity/heritage-resource/multiple history. The paper is concerned with the different possibilities adopted by teachers, considering that the current situation corresponds to the consumer collective identity and analyzing its consequences. Responding to this, we show two coherent alternatives to history teaching. Both are useful to education process, depending on our comprehension of what history is and what its usefulness means.